Possibilities for resource sharing among public libraries in Metro Manila - Yabes, Janette G.
This paper intends to ascertain the possibilities of resource sharing among public libraries in Metro Manila. It attempts to find out the existing resources and facilities available in these libraries and to determine if these libraries are willing to participate in any resource sharing activities; to determine the type of resource sharing activities these libraries are willing to engage in and to determine the possible benefits these libraries will acquire from the proposed resource sharing arrangement.